PROBLEMS OF DISTANCE LEARNING IN THE LMS MOODLE ENVIRONMENT THROUGH THE EYES OF STUDENTS OF MOSCOW AVIATION INSTITUTE DURING QUARANTINE (SELF-ISOLATION) - Ukhov, Peter; Ryapukhin, Anatoly; Biriukova, Natalia; Biryukova, Anna; Dmitrochenko, Boris (Revista Inclusiones, 2019)
Information technology of the XXI century has influenced the work of universities around the world. Distance learning is not inferior to traditional forms of education at all, since students can also interact with teachers and classmates throughout the entire educational process. The Learning Management System (LMS) is currently a vital component of university e-learning infrastructure. Using LMS to create, manage and conduct educational and training programs allows educational institutions to create multimedia learning content that is comprehensive and practical. In connection with the coronavirus pandemic on March 17, 2020, Moscow Aviation Institute (National Research University) (MAI) completely switched to the distance learning mode, like other universities. When studying the Moodle training system, on the basis of which the educational system is built, there were problems to ensure the safety of students: from basic authentication to unintended information functions. When describing the problems of the LMS in the article, special attention is paid to the security problems of authentication and user identification. The article provides recommendations for resolving these problems.